Synergistic effect of stromelysin-1 (matrix metalloproteinase-3) promoter 5A/6A polymorphism with smoking on the onset of young acute myocardial infarction - Liu, Ping-Yen; Chen, Jyh-Hong; Li, Yi-Heng; Wu, Hua-Lin; Shi, Guey-Yueh (Thrombosis and Haemostasis, 2003)
The objective of this study was to elucidate the association between the polymorphism of stromelysin-1, also called matrix metalloproteinases-3 (MMP-3), and smoking in the pathogenesis of young acute myocardial infarction (MI).Plaque rupture is well established as a critical factor in the pathogenesis of acute MI. MMP-3 can degrade extracellular matrix and are identified extensively in human coronary atheroslcerotic plaques, and may contribute to the weakening of the cap and subsequent rupture.We studied 150 consecutive patients with acute MI onset at age under 45 years (84% men) and 150 sex- and age-matched control subjects. 5A/6A genotype in the stromelysin-1 promoter was determined using polymerase chain reaction and direct sequencing.Results show that the frequency of the 5A allele and the prevalence of 5A/5A + 5A/6A genotypes were both significantly higher in the young MI than the control group (35.0% vs.20.0%, odds ratio [OR] 2.15,95% confidence interval [CI] 1.30 to 6.80, p<0.001; 44.7% vs. 27.4%, OR 2.19, 95% CI 1.21 to 3.98, p=0.009). Multiple logistic regression analysis showed that the 5A allele was an independent risk factor (OR 2.36, 95% CI 1.24 to 5.90, p=0.008) as were as smoking (OR 3.92, 95% CI 1.75 to 9.21, p=0.001), diabetes mellitus (OR 3.51, 95% CI 1.41 to 6.32, p=0.0068) and hypertension (OR 1.85, 95% CI 1.35 to 4.33, p=0.0025) for the premature onset of MI. Compared to 6A/6A subjects, among patients who did not smoke, the 5A allele poly-morphism was associated with a higher risk of MI at a young age (OR 2.69, 95% CI 1.3 to 8.6), but smoking carriers of the 5A allele had a significantly 10-fold higher risk of MI (OR 9.98, 95% CI 2.3 to 12.5).We can conclude that there was a significant association between the 5A/6A polymorphism in the promoter region of stromelysin-1 gene and young MI in Taiwan. A synergistic effect between smoking and this polymorphism for the premature onset of MI had been shown in this study.
Keywords: Acute myocardial infarction; polymorphism; smoking; matrix metalloproteinase